2014
DOI: 10.1016/j.ejon.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine gene variations associated with subsyndromal depressive symptoms in patients with breast cancer

Abstract: Purpose This study explored the relationships between variations in cytokines genes and depressive symptoms in a sample of patients who were assessed prior to and for six months following breast cancer surgery. Phenotypic differences between Resilient (n=155) and Subsyndromal (n=180) depressive symptom classes, as well as variations in cytokine genes were evaluated. Method Patients were recruited prior to surgery and followed for six months. Growth mixture modeling was used to identify distinct latent classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 70 publications
2
30
1
1
Order By: Relevance
“…Consistent with the findings of Saad et al on the association between TNF-α (rs1799964) and the development of subsyndromal depression [75], a corresponding decreased odds of higher anxiety class was also observed with the SNP (rs1799964) among breast cancer patients undergoing breast surgery [82]. On the other hand, this study also observed that TNF-α (rs3093662) was associated with higher odds of developing anxiety therefore suggesting that TNF-α SNPs may serve as important predictive marker of increased susceptibility to psychological distress among breast cancer patients.…”
Section: Psychological Distresssupporting
confidence: 81%
See 4 more Smart Citations
“…Consistent with the findings of Saad et al on the association between TNF-α (rs1799964) and the development of subsyndromal depression [75], a corresponding decreased odds of higher anxiety class was also observed with the SNP (rs1799964) among breast cancer patients undergoing breast surgery [82]. On the other hand, this study also observed that TNF-α (rs3093662) was associated with higher odds of developing anxiety therefore suggesting that TNF-α SNPs may serve as important predictive marker of increased susceptibility to psychological distress among breast cancer patients.…”
Section: Psychological Distresssupporting
confidence: 81%
“…The study also demonstrated that SNPs in Interferon Gamma Receptor 1 (IFNGR1, rs9376268) and IL6 (rs2069840) were associated with the development of subsyndromal depressive symptoms. Nevertheless, in contrast to the findings by Kim et al [71] which demonstrated a significant association between IL1B and depression, similar findings could not be confirmed by Saad et al [75]. Furthermore, the associations between SNPs in cytokines and depression appeared to vary depending on the cancer type; for instance, Duun et al [76] reported an association between two TNF-α SNPs (rs2229074, rs1800629) and depression in patients with various types of cancer (breast, prostate, lung and brain) and their family care givers.…”
Section: Psychological Distresscontrasting
confidence: 56%
See 3 more Smart Citations